Drawing from motion capture : developing visual languages of animation - Megre, Ricardo de Sá Carneiro (2022)
The work presented in this thesis aims to explore novel approaches of combining motion capture with drawing and 3D animation. As the art form of animation matures, possibilities of hybrid techniques become more feasible, and crosses between traditional and digital media provide new opportunities for artistic expression. 3D computer animation is used for its keyframing and rendering advancements, that result in complex pipelines where different areas of technical and artistic specialists contribute to the end result. Motion capture is mostly used for realistic animation, more often than not for live-action filmmaking, as a visual effect. Realistic animated films depend on retargeting techniques, designed to preserve actors performances with a high degree of accuracy. In this thesis, we investigate alternative production methods that do not depend on retargeting, and provide animators with greater options for experimentation and expressivity. As motion capture data is a great source for naturalistic movements, we aim to combine it with interactive methods such as digital sculpting and 3D drawing. As drawing is predominately used in preproduction, in both the case of realistic animation and visual effects, we embed it instead to alternative production methods, where artists can benefit from improvisation and expression, while emerging in a three-dimensional environment. Additionally, we apply these alternative methods for the visual development of animation, where they become relevant for the creation of specific visual languages that can be used to articulate concrete ideas for storytelling in animation.